New carbenicillin-hydrolyzing beta-lactamase (CARB-7) from Vibrio cholerae non-O1, non-O139 strains encoded by the VCR region of the V. cholerae genome - Melano, Roberto (2002)
Fil: Melano, Roberto. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Bacteriología. Servicio de Antimicrobianos; Argentina.